Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation. Issue 1 (28th December 2022) - Chin, Andrew; Molloy, Molloy John; Cameron, Darren; Day, Jon C.; Cramp, Jessica; Gerhardt, Karin G.; Heupel, Michelle R.; Read, Mark; Simpfendorfer, Colin A.
Abstract: Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection, contribution, potential impact, risk, threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation. Abstract : Marcos conceptuales y preguntas clave para evaluar la contribución de las áreas marinas protegidas a la conservación de tiburones y rayas Resumen: Las áreas marinas protegidas (AMP) son herramientas importantes para manejar la declinación mundial de tiburones y rayas, por lo que se han establecido parques marinos y santuarios de diversas configuraciones para conservar las poblaciones de tiburones. Sin embargo, el análisis de su eficiencia está compuesto por una terminología inconstante, la falta de estrategias estandarizadas para evaluar cómo las AMP contribuyen a la conservación de tiburones y rayas, y una ambigüedad sobre cómo integrar la información sobre movimientos en los procesos de evaluación. Diseñamos un marco conceptual para estandarizar los términos más importantes (p. ej.: protección, contribución, impacto potencial, amenaza, riesgo ) y usamos el concepto de riesgo de portafolio para identificar los atributos clave de los tiburones y las rayas (activos), las amenazas que enfrentan (riesgo de portafolio) y el papel específico que juegan las AMP en la mitigación del riesgo (seguro). La información sobre los movimientos puede integrarse al proceso al guiar la exposición y mitigación del riesgo con las AMP. El marco conceptual es operado con el planteamiento de ocho preguntas clave que invitan a los practicantes a considerar el enfoque de la evaluación, el tipo de AMP y su propósito, gama de amenazas existentes y potenciales, la biología y ecología de las especies, y los contextos operativos y de manejo. Finalmente, las contribuciones que tienen las AMP a la conservación de los tiburones y las rayas difieren de acuerdo con un conjunto complejo de factores naturales y humanos e interacciones que deberían considerarse cuidadosamente en el diseño, implementación y evaluación de la AMP. 【摘要】: 海洋保护区(marine protected area, MPA)是解决全球鲨鱼和鳐鱼种群下降问题的关键工具, 目前已经建立了各种配置的海洋公园和鲨鱼保护区来保护鲨鱼种群。然而, 由于术语不统一、缺乏标准化方法来评估MPA对鲨鱼和鳐鱼的保护贡献, 以及对如何在评估过程中整合运动数据的认识不清晰, 对MPA保护成效的评估仍面临阻碍。我们设计了一个概念框架来标准化关键术语(如保护、贡献、潜在影响、风险、威胁), 并使用组合风险的概念来确定鲨鱼和鳐鱼的关键属性(资源)、它们面临的威胁(组合风险), 以及MPA在减缓风险方面的具体作用(保障)。运动数据通过提供风险暴露和基于MPA的风险减缓的信息, 从而被整合到这个过程中。该框架的实施基于提出的8个关键问题, 以推动保护实践者考虑评估范围、MPA类型和目的、现有及潜在威胁的范围、物种生物学和生态学, 以及管理和操作背景。最终, 基于一系列复杂的人类与自然因素及其相互作用, MPA对鲨鱼及鳐鱼的保护贡献可能有所不同, 因此, 在MPA设计、实施和评估中应仔细考虑这些因素。【翻译:胡怡思;审校:聂永刚】